How prepared are healthcare professionals for delivering physical activity guidance to those with diabetes? A formative evaluation - N. Kime; A. Pringle; S. Zwolinsky; D. Vishnubala (BMC, 2020)
Abstract Background Physical activity is recognised as important for diabetes management and improved overall health of individuals with diabetes, yet many adults with diabetes are inactive. Healthcare professionals have been identified as key to promoting physical activity, including individuals with diabetes, but are ill-prepared to deliver this. Our paper evaluates the barriers/facilitators of healthcare professionals' delivery of physical activity guidance to adults with diabetes and aims to inform efforts to investigate and enhance their preparedness to promote physical activity. Methods A sequential mixed method, two-phase design was adopted involving a purposeful sample of healthcare professionals. Phase one was an online pilot survey designed to test assumptions around healthcare professionals' knowledge, training and preparedness to deliver physical activity guidance. Phase two comprised eighteen semi-structured interviews, thematically analysed to provide an in-depth exploration of healthcare professionals' experiences of delivering physical activity guidance to adults with diabetes. Results Healthcare professionals are committed to promoting physical activity to adults with diabetes and are reasonably confident in giving basic, generic guidance. Yet, significant challenges prevent them from achieving this in their practice, including: lack of education and training around physical activity, diabetes and health; ignorance of recommended physical activity and diabetes guidelines; lack of awareness of referral options; limited time and accessibility to appropriate resources. Nevertheless, healthcare professionals believed discussions around physical activity needed to be an integral part of consultations, incorporating improved communication strategies for conveying key physical activity messages. Conclusions HCPs have a key role in the promotion of physical activity to people with long-term conditions such as diabetes and they are identified within both the strategic policy context and national interventions for physical activity. Yet, this study indicated that HCPs face multiple and at times complex barriers to physical activity promotion generally and with diabetes patients. Conversely HCPs also reported what works, why and how, when promoting physical activity. Rich information derived from the day-to-day, working healthcare professional is integral to shaping future practices going forward. The bottom up, iterative design adopted in this study provides an approach to tap into this information.